Effects of coenzyme Q10 on cardiovascular and metabolic biomarkers in overweight and obese patients with type 2 diabetes mellitus: a pooled analysis - Huang H (Dove Medical Press, 2018)
Haohai Huang,1 Honggang Chi,2 Dan Liao,3 Ying Zou2,4 1Department of Clinical Pharmacy, Dongguan Third People’s Hospital, Affiliated Dongguan Shilong People’s Hospital of Southern Medical University, Dongguan, Guangdong, China; 2Department of Traditional Chinese Medicine, Scientific Research Platform, The Second Clinical Medical College, Guangdong Medical University, Dongguan, China; 3Department of Gynaecology & Obstetrics, Dongguan Third People’s Hospital, Affiliated Dongguan Shilong People’s Hospital of Southern Medical University, Dongguan, Guangdong, China; 4Key Laboratory for Medical Molecular Diagnostics of Guangdong Province, Guangdong Medical University, Dongguan, Guangdong, China Background: The potential effects of coenzyme Q10 (CoQ10) supplementation in overweight/obese patients with type 2 diabetes mellitus are not fully established. In this article, we aimed to perform a pooled analysis to investigate the effects of CoQ10 intervention on cardiovascular disease (CVD) risk factors in overweight/obese patients with type 2 diabetes mellitus (T2DM). Methods: MEDLINE, Embase, and Cochrane databases were searched for randomized controlled trials that evaluated the changes in CVD risk factors among overweight and obese patients with T2DM following CoQ10 supplementation. Two investigators independently assessed articles for inclusion, extracted data, and assessed risk of bias. Major endpoints were synthesized as weighted mean differences (WMDs) with 95% CIs. Subgroup analyses were performed to check the consistency of effect sizes across groups. Publication bias and sensitivity analysis were also performed. Results: Fourteen eligible trials with 693 overweight/obese diabetic subjects were included for pooling. CoQ10 interventions significantly reduced fasting blood glucose (FBG; –0.59 mmol/L; 95% CI, −1.05 to –0.12; P=0.01), hemoglobin A1c (HbA1c; –0.28%; 95% CI−0.53 to –0.03; P=0.03), and triglyceride (TG) levels (0.17 mmol/L; 95% CI, −0.32 to –0.03; P=0.02). Subgroup analysis also showed that low-dose consumption of CoQ10 (<200 mg/d) effectively reduces the values of FBG, HbA1c, fasting blood insulin, homeostatic model assessment of insulin resistance, and TG. CoQ10 treatment was well tolerated, and no drug-related adverse reactions were reported. Conclusion: Our findings provide substantial evidence that daily CoQ10 supplementation has beneficial effects on glucose control and lipid management in overweight and obese patients with T2DM. Keywords: coenzyme Q10, type 2 diabetes mellitus, cardiovascular risk factors, lipids, glucose, obesity